Trimethoprim-sulphamethoxazole in the treatment of persistent diarrhoea: a double blind placebo controlled clinical trial. Issue 6 (June 1995) - Alam, N H; Bardhan, P K; Haider, R; Mahalanabis, D
Abstract : The efficacy of an absorbable antimicrobial agent trimethoprim-sulphamethoxazole (TMP-SMX) in the management of children with persistent diarrhoea was evaluated in a double blind, randomised, and placebo controlled trial. Of the 55 patients studied, 28 received TMP-SMX, and 27 received placebo. A trend in stool weight reduction was observed from the third day after the drug was started, and the reduction was statistically significant on day 6 and day 7. However, the difference in total stool output (g/kg) up to day 7 was not significantly different between the two groups. The proportion of children whose diarrhoea resolved by day 7 (therapeutic success) was significantly more in the treatment group compared with the placebo group (23 v 15). Additionally, mean duration of diarrhoea in the group that received TMP-SMX was less compared with the placebo group (6.0 v 8.3 days); this difference, however, was not significant. Hospital infection (probably nosocomial infection) was significantly less in the TMP-SMX treated group (1 v 10). The results of our study indicate that TMP-SMX has a clinical benefit in respect of reducing the stool output, and higher recovery rate within seven days of treatment. In addition, it prevented possible hospital acquired infection.